Hoja de ruta para acceder a instrumentos de financiamiento públicos y/o privados para lograr los compromisos del Acuerdo Cero Deforestación de la Cadena Láctea - Marulanda, Jose; Borda, Carlos; Vanegas, Martha (2023)
This roadmap presents a series of stages and activities that are recommended to access to financing sources that encourage the adoption of practices associated with Zero Deforestation livestock farming models. The first part of the roadmap consists of categorization of the level of deforestation risk in the supply chain based on the self-analysis of the direct and indirect supply networks. The second part consists of carrying out a prospective analysis of requirements that can be developed in the short, medium and long term in order to structure the demands for zero deforestation activities and practices that will subsequently be susceptible to being financed. The third part of the roadmap consists of a portfolio of financing instruments for corrective actions for the transition towards zero deforestation livestock farming and the transition towards restoration and conservation models. This work contributes to compliance with the Zero Deforestation and No Transformation of Paramos Agreement for the Colombian dairy industry, which seeks to eliminate the footprint of deforestation in its production and supply chain, and thus contribute to the achievement of the country's goals in reducing deforestation.